Effect of Jungga Orange Peel Essential Oil (Citrus Jambhiri) on Platelet Function in Male Rats Given High Intensity Physical Activity - Novita Sari Harahap; Diky Setya Diningrat; Yetty Machrina (UNIB Press, 2022)
Physical activity is one of the stress factors that can provide physiological changes to the function of the hematological system such as changes in platelet count. Physical activity can produce free radicals that can result in cell damage including platelets. Platelets play a role in the hemostasis process, If the platelet count is too low, it can cause excessive bleeding. However, if there is an increase in platelet count too high, it can cause thrombosis that can inhibit blood vessels. Antioxidants have a protective effect on cells and eliminate free radicals. The objective of this research was to ascertain the reaction of platelets to the injection of jungga orange peel essential oil (citrus jambhiri) in male rats that were subjected to strenuous exercise. Twenty male rats (3-4 months old, 180-200 grams) of the Wistar strain of the white rat (Rattus norvegicus) were used in the experiment. Using a random number generator, 20 white rats were split into two groups. In group P1, the rats swam for 50 minutes, three times a week, for four weeks. In group P2, the rats swam for 50 minutes, three times a week, for four weeks, and were also given 0.05 milliliters of jungga orange peel essential oil every hour prior to swimming. Based on these findings, it appears that there is a statistically significant difference between the P1 and P2 groups in terms of the average platelet count, with the P2 group exhibiting a decline in platelet count. Antioxidant substances contained in the essential oil of jungga orang have the ability to inhibit the decline in platelet function after high-intensity physical activity.